Synthesis and Characterization of Carbon Fibers and their Application in Wood Composites - Gupta, Arun; Khan, Tanveer Ahmed; Saidatul Shima, Jamari; Rajan, Jose; Mohammed, Nasir; Anuj, Kumar (North Carolina State University, 2013)
Carbon fibers were synthesized using a low-cost, economical method. Fresh rubber wood fibers (Hevea brasiliensis) were burned using a furnace in an inert condition at 350 to 450 oC for 2-4 hours, and after that the fibers were ground at 18000 rpm for 20 to 40 seconds. The effect of carbon fibers as a reinforcement agent on mechanical, physical, and morphological properties was investigated. In the composite preparation, carbon fiber dosages (0, 0.1, 0.25, and 0.5 wt.%) were used as variable factors, along with a urea formaldehyde content of 10%. The morphology of the specimens was characterized using X-ray diffraction (XRD), Thermogravimetric analysis (TGA), and Field Emission Scanning Electron Microscopy (FESEM). The mechanical tests indicated that when carbon fibers were added, the modulus of rupture (MOR) and internal bonding strength (IB) improved significantly. From the TGA graph it was observed that the thermal stability of the composites based on carbon fiber was higher than composites without it. The thermocouple readings showed that at a higher loading of carbon, the core temperature of the board increased faster than for the control board.